Countermeasures criminal action of corruption in banking in the lending of credits - NURHAYATI, RATNA; GUMBIRA, SENO WIBOWO (The journal of contemporary issues in business and government, 2021)
This article discusses the prevention of corruption in the banking sector in credit extension that occurs in Indonesia. In the discussion of this article, it is known that although almost every bank has implemented the principle of prudence and trust in providing credit, if it is not followed by building Good Corporate governance, the deviation will continue and that this principle does not guarantee that there are no irregularities in the implementation of credit distribution because of the large number of factors, and the dominant factor is the problem of the welfare of the bank officials and employees. Moreover, almost all banks use the services of outsourcing workers, and in the case of the criminal act of corruption in resolving bad/problematic credit at state-owned banks, it is appropriate to see the reasons for the bad credit.